Пам’яті Ернста Анатолійовича Пашицького (1936–2023) - Galkina, E.G.; Pentegov, V.I.; Semenov, A.V.; Ryabchenko, S.M.; Bondar, M.V. (Publishing house "Academperiodika", 2023)
On February 14, 2023, Ernst Anatoliyovych Pashitskii, brilliant scientist, Professor, Doctor of physical and mathematical sciences, and Corresponding Member of the National Academy of Sciences of Ukraine, passed away in his 87th year.